Your chemical science thesis : an introductory guide to writing up your research project - Mansfield, Natalie (Royal Society of Chemistry, 2008)
THIS PRODUCT IS SOLD IN PACKS OF TEN ONLY * Writing your thesis will be a major task within your research career. In particular, the Chemical Sciences thesis will generally fit into a certain format and this introductory guide is ideal for anyone currently writing, or about to write, this type of thesis. Divided into six chapters, this no fuss booklet provides an informative step-by-step guide on everything you need to know, from the practicalities of actually getting started, through to completion and submission. The guide follows a logical format and the text itself broken up with helpful nu.